2009
DOI: 10.3844/ajassp.2009.869.875
|View full text |Cite
|
Sign up to set email alerts
|

Bio-oils from Pyrolysis of Oil Palm Empty Fruit Bunches

Abstract: Problem Statement: The palm oil industry generates an abundance of oil palm biomass such as the mesocarp fibre, shell, empty fruit bunch (EFB), frond, trunk and palm oil mill effluent (POME). For 80 million tonnes of fresh fruit bunch (FFB) processed last year, the amount of oil palm biomass was more than 25 million tones. The objectives of this study were to: (i) Determine the effect of various pyrolysis parameters on product yields and (ii) Characterise liquid product obtained under different condition. Appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 20 publications
4
47
3
1
Order By: Relevance
“…The percent volatile of pellets obtained in this study (Table 2) is lower than that obtained by Sukiran et al (2009) for EFB pellets, for which the reported value is 81.90%. And this difference can be again attributed to different growing conditions of oil palm (Chiew and Shimada, 2013).…”
Section: Table 5 Pellet Consumption Rates Characteristics Of the Ascontrasting
confidence: 42%
“…The percent volatile of pellets obtained in this study (Table 2) is lower than that obtained by Sukiran et al (2009) for EFB pellets, for which the reported value is 81.90%. And this difference can be again attributed to different growing conditions of oil palm (Chiew and Shimada, 2013).…”
Section: Table 5 Pellet Consumption Rates Characteristics Of the Ascontrasting
confidence: 42%
“…Tables Table 1 Overview of Fast Pyrolysis Developments. Biomass Type Biomass woody iroko, albizia, beech, spruce [183], pine [92,110,114], white oak [113], larch [111], sawtooth oak [100], mallee [95,98,99], bamboo sawdust [184], pine, forest residues and eucalyptus [50], waste furniture sawdust [103] agricultural residues empty fruit bunches [66,80,81,185], soyabean harvesting residues [72], cotton-stalk [107], corn straw [186], corn cobs and stover [187], rice husk [102,105], rice straw [184], corncob, straw and oreganum stalks [188], maize stalks [106] industrial byproducts grape skins and seeds [94], barley biomass/product streams [189], lignin [91]. non-woody switchgrass [109], jute-stick [190], alfalfa, reed canary grass, eastern gammagrass [191], miscanthus [104], barley straw, rapeseed straw, reed canary grass [50] waste products guayule [192], soybean oil [193], fish waste [194], sewage sludge [195], chicken and turkey litter [196,197].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, thermo-chemical technology for converting PEFB into energy has been studied in laboratory or bench scale. Many studies nowadays focus on the pyrolysis of PEFB for bio-oil production in lab-scale, both fixed bed and fluidized bed reactor and it can be evidenced that the maximum yield of bio-oil produced from pyrolysis of PEFB without catalysts occurs at the temperature of about 500 °C and the lower heating value of bio-oil is approximately 20 MJ/kg (Abdullah & Bridwater, 2006;Abdullah et al, 2007;Azizan et al, 2009;Sukiran et al, 2009;Yang et al, 2006). The utilization of catalyst can promote the pyrolysis reaction and the maximum bio-oil can be obtained at lower temperature of about 300-350 °C with shorter residence time (Amin & Asmadi, 2008).…”
Section: Pefb Utilization For Energetic Purposesmentioning
confidence: 99%